Studies in biblical law : from the Hebrew Bible to the Dead Sea scrolls - Brin, Gershon (Journal for the study of the Old Testament. Supplement series, 1994)
Gershon Brin examines the development of biblical law, suggesting that it may be due to different authors with different legal outlooks, or that the differing policies were required in response to different social needs, etc. Biblical laws appearing in the Dead Sea Scrolls literature are treated in a separate unit. Study of this subject can shed light both on the biblical laws as such, as well as on the manner of their reworking by the Judaean Desert sect. Brin also discusses here questions of the style, the idea, and the historical and ideological background underlying the reworking of these.